ANALISIS GAYA KEPEMIMPINAN DALAM MENINGKATKAN MOTIVASI KERJA PEGAWAI PADA DINAS PEKERJAAN UMUM KOTA KENDARI - Bakti Bakti; La Ode Muhammad Elwan (Universitas Halu Oleo, 2019)
Thus, this research aims to: (1) To know the leadership style of the Head of Department to improve the employee motivation in Kendari Public Works Department. (2) To know the work motivation of employees at the Kendari Public Works Department.This research is qualitative research, which is research procedure that produces an analytical description of the written word and the behaviour of the object being observed. In this research, the determination of the informant set intentionally. Data was collected using three techniques, namely, observation, interviews and document analysis.The results showed that: 1) the dominant leadership style adopted by the Head of Department of Kendari Public Works is democratic leadership. This is based on interviews and analysis according to each indicator - free leadership style, autocratic, bureaucratic and undemocratic. All informants stated that the Head of the Kendari Public Works Department divides the tasks to subordinates in a fair and equitable, and using collaboration and discussion within the team to discuss the work and decision-making, this is in accordance with democratic leadership style indicator. While other leadership styles, there are several indicators that are not met. 2) Democratic leadership style adopted by the Kendari Head of the Public Works Department has not fully improved employee motivation. This is according to the results of the analysis and interviews on each indicator. As; still lack some office facilities and field facility at the sub-variable leadership attention on employee work environment; still, a lack of employees who follow the Structural Training, take formal education (bachelor and master) on the sub-variable provide opportunities for advanced. This is an indicator that can reduce the work motivation of employees of the Kendari City Public Works Department. Keywords: Leadership Style, The Work Motivation